(untitled) (World Economics and Finance Bulletin, 2026)
This paper examines labor market transformations in developed countries (2022-2030) in light of artificial intelligence applications, focusing on the future of jobs and its impact on traditional employment opportunities. This study found that artificial intelligence has brought about fundamental changes at varying rates globally, leading to the automation of jobs and the emergence of new ones requiring specialized skills, while considering ethical, security, and legislative aspects, and warning against challenges such as bias in algorithms and privacy issues. It also reviews international and regional efforts in regulating artificial intelligence, emphasizing the need to balance promoting innovation and protecting fundamental rights and security.